2020
DOI: 10.3389/fgene.2020.571694
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of the Callorhinchus Vertebral Column (Holocephali; Chondrichthyes)

Abstract: Members of the Chondrichthyes (Elasmobranchii and Holocephali) are distinguished by their largely cartilaginous endoskeletons, which comprise an uncalcified core overlain by a mineralized layer; in the Elasmobranchii (sharks, skates, rays) most of this mineralization takes the form of calcified polygonal tiles known as tesserae. In recent years, these skeletal tissues have been described in ever increasing detail in sharks and rays, but those of Holocephali (chimaeroids) have been less well-studied, with confl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 77 publications
(184 reference statements)
3
33
0
Order By: Relevance
“…Previous studies showed poorly developed cartilaginous tissue in the posterior vertebrae of juvenile H. colliei, where histology displayed no sign of modified cartilaginous matrix that could be linked to cartilage mineralization (Debiais-Thibaud, 2019). However, more recent publications pointed out the thin layer of mineralized matrix in the synarcual of the elephant shark Callorhinchus milii (Pears et al, 2020) and recognized thin tesserae in the adult C. milii and rabbit fishes Chimaera monstrosa (Pears et al, 2020;Seidel et al, 2020). In our H. colliei sample, we detect a similar thin layer of mineralized tissue in the synarcual of a hatchling and a juvenile specimen (Figures 4A,G).…”
Section: Synarcual Mineralization In Hydrolagus Collieisupporting
confidence: 77%
See 4 more Smart Citations
“…Previous studies showed poorly developed cartilaginous tissue in the posterior vertebrae of juvenile H. colliei, where histology displayed no sign of modified cartilaginous matrix that could be linked to cartilage mineralization (Debiais-Thibaud, 2019). However, more recent publications pointed out the thin layer of mineralized matrix in the synarcual of the elephant shark Callorhinchus milii (Pears et al, 2020) and recognized thin tesserae in the adult C. milii and rabbit fishes Chimaera monstrosa (Pears et al, 2020;Seidel et al, 2020). In our H. colliei sample, we detect a similar thin layer of mineralized tissue in the synarcual of a hatchling and a juvenile specimen (Figures 4A,G).…”
Section: Synarcual Mineralization In Hydrolagus Collieisupporting
confidence: 77%
“…The cells located on the perichondrial side of this line are enclosed in lacunae in a matrix of cartilaginous nature [as supported by positive Alcian blue staining (Figures 4F,H)], although the cells are flattened ( Figures 4E' ,G'). Moreover, no cells can be observed fully embedded in the mineralized cartilaginous matrix, either at the hatching or juvenile stage and the mineralized layer appears discontinuous (Figures 4G' ,H), supporting the presence of aligned tesserae as described in other holocephalan species (Pears et al, 2020).…”
Section: Synarcual Mineralization In Hydrolagus Collieisupporting
confidence: 74%
See 3 more Smart Citations